Fatigue life assessment of centrifugal compressor impeller based on FEA. (February 2016) - Liu, Shujie; Liu, Chi; Hu, Yawei; Gao, Sibo; Wang, Yifan; Zhang, Hongchao
Abstract: Fatigue life assessment of centrifugal compressor impellers has been a critical issue in industrial practice and application. In this paper, both centrifugal load and aerodynamic load have been considered in the analysis of the impeller life using finite element analysis (FEA). The analysis showed the regions of stress concentration and the mean stress of the finite element at the maximum stress point. The S–N curve of the impeller is therefore fitted by a computational model. The model is proved to be reliable by comparing the computed results with the experimental data. Thereby the failure mechanism of the impeller can be expressed analytically and its reliability can be assessed online. Highlights: Full sized model of the centrifugal compressor impeller is built based on the entity. The impeller is loaded by the combination of centrifugal load and aerodynamic load. The fitted S-N curve is obtained from experimental data and results of Finite Element Analysis. The estimated fatigue lives of the centrifugal compressor impeller at different load amplitudes are approximate to the experimental results.